Influence of palm oil mills effluent (POME) sludge vermicomposting on soil physicochemical properties and Zea mays growth performances - Abd Karim, Khairul Najmuddin; Md Isa, Isharudin; Ramlan, Mohd Fauzi; Mohamad, Azham; Khairuddin, Mohd Nizar; Ariffin, Mohd Rizal (Chaoyang University of Technology, 2022)
Discharging the palm oil mill effluents (POME) might result in environmental pollution, thus the POME wastes that had high total solids, abundant in oil palm mills, potential to be utilized as an organic amendment, vermicompost or treated POME sludge (TPS). The objectives of this study are to determine the best treatment effect of organic amendments and Zea mays growth performances, and to analyse the soil physicochemical properties after application of treatments after harvesting. This experiment was carried out in Randomized Completely Block Design (RCBD) with 4 treatments and 6 replications. The treatments consisted of; treatment 1: Control, treatment 2: 2 kg FVC, treatment 3: 2 kg TPS and treatment 4: 1 kg FVC and 1 kg TPS. Based on the result, 2 kg FVC (T2) treatment showed significant improvement in soil physical properties and soil shear strength. Cation exchange capacity (CEC), nutrients availability and and Zea mays growth performances were also improved in this experiment. For shear strength analysis, T4 treatment showed high normal stress at 319.4 kN/m2. In conclusion, FVC organic fertilizer and mixed FVC and TPS indicated the best amendment in improving soil physicochemical and enhanced Zea mays growth performance and it is cost effective and environmentally friendly.